A study on the policies and procedures of anti-money laundering framework practiced by Am Assurance / Norhazwani Hasinah Haniffuddin - Haniffuddin, Norhazwani Hasinah (Faculty of Business and Management, 2009)
Money laundering is the process by which criminals attempt to conceal the true origin and ownership of the proceeds of their unlawful activities such as smuggling offence, false trading, bucketing, inducing persons to invest money, dangerous drugs, kidnapping, theft, robbery, slavery, extortion, terrorism and others. The issue is how the launderers clean their “dirty money” from an illegal business through bought an Insurance policy. The objectives of this study to know the meaning of the money laundering because money laundering and terrorist financing is a worldwide phenomenon besides it is very important information and serious case but it is seemed less popular and not everybody knows about this topic. Then, to identify the Policies and Procedures of Anti-Money Laundering Practiced by Am Assurance and to identify the manner how Money Laundering in Insurance industries. In order to evaluate the Policies and Procedures of Anti-Money Laundering Framework Practiced by Am Assurance, the researcher has obtained data from primary and secondary sources. Primary source is obtained from the conduct minor interview with the branch manager, agency manager, agents and staff of company in order to get more information regarding issues of Anti-Money Laundering. Meanwhile, secondary source are obtained from both internal and external. Internal source obtained from published material from the company such as financial statement, Private and confidential AMLA Framework by BNM and website of the company. Basically, for external sources obtained from book, journal and article from internet. During the researcher in the Am Assurance, researcher found the agent of Am Assurance does not do further investigation of their clients’ background if in general the client’s portfolio as provided involving with legal activities or business and do not practiced “Know Your Customer” even though BNM has introduced the circular and guideline of “Know Your Customer”.